2021
DOI: 10.1101/2021.03.08.21252788
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 antibody prevalence and determinants of six ethnic groups living in Amsterdam, the Netherlands: a population-based cross-sectional study, June-October 2020

Abstract: Background Ethnic minorities have higher rates of SARS-CoV-2 diagnoses, but little is known about ethnic differences in past exposure. We aimed to determine whether prevalence and determinants of SARS-CoV-2 exposure varied between six ethnic groups in Amsterdam, the Netherlands. Methods Participants aged 25-79 years enrolled in a population-based prospective cohort were randomly selected within ethnic groups and invited to test for SARS-CoV-2-specific antibodies and answer COVID-19 related questions. We estim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 35 publications
1
18
1
2
Order By: Relevance
“…Survival bias among the retrospectively-enrolled hospitalised participants may have caused an underestimation of time to complete recovery in those with severe/critical disease, although results were comparable when restricting our analyses to prospectively identified participants. Questionnaires in languages other than Dutch and English were not offered, therefore individuals with a migration background, who have been disproportionally affected by COVID-19, also in Amsterdam[25, 26], were underrepresented in this cohort. Furthermore, misclassification bias may have resulted from using ICU admission as a proxy for critical disease; suitability for ICU admission is also judged by the patient’s chance of survival; indeed, those with critical disease tended to be younger and have a lower BMI than those in the severe group.…”
Section: Discussionmentioning
confidence: 99%
“…Survival bias among the retrospectively-enrolled hospitalised participants may have caused an underestimation of time to complete recovery in those with severe/critical disease, although results were comparable when restricting our analyses to prospectively identified participants. Questionnaires in languages other than Dutch and English were not offered, therefore individuals with a migration background, who have been disproportionally affected by COVID-19, also in Amsterdam[25, 26], were underrepresented in this cohort. Furthermore, misclassification bias may have resulted from using ICU admission as a proxy for critical disease; suitability for ICU admission is also judged by the patient’s chance of survival; indeed, those with critical disease tended to be younger and have a lower BMI than those in the severe group.…”
Section: Discussionmentioning
confidence: 99%
“…In high-income countries, migrant and minority ethnic populations have been shown to be at increased risk of confirmed SARS-CoV-2 infection 4 , 5 , 6 . In the Netherlands, higher infection seroprevalence was observed among persons of Ghanaian origin after the first wave of infections [7] . In line with the crucial role of human behaviour, previous studies indeed provide evidence to suggest lower uptake of preventive measures in migrant and minority ethnic populations [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research on smaller migrant and minority ethnic populations and in other country settings is scarce. The research project ‘Ethnicity and COVID-19: Epidemiology and control measures’ initiated at the request of The Netherlands Organization for Health Research and Development aims to establish a comprehensive view on COVID-19 amongst migrant and minority ethnic populations in The Netherlands and formulate policy recommendations [7] . Specifically, this qualitative study intended to gain an understanding of smaller, albeit substantial, migrant and minority ethnic populations with varying migration backgrounds, migration motives and length of stay in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%
“…Participant characteristics have been described in detail previously. 12 S1. The age and sex distribution of participants who returned by March 31, 2021 were comparable to participants who did not; however, participants who did not return were more likely to be first generation migrants, not be employed, and have a lower educational and occupational level, difficulties with the Dutch language, lower health literacy, and SARS-CoV-2 antibodies at the first visit (Table 1).…”
Section: Study Populationmentioning
confidence: 99%
“…A large population-based study conducted after the first wave of the SARS-CoV-2 epidemic found that only individuals of Ghanaian origin were at higher risk of past exposure to SARS-CoV-2, whereas individuals of South-Asian Surinamese, African Surinamese, Turkish, or Moroccan origin had a similar risk compared with individuals of Dutch origin. 12 Given the potential for ethnic differences during the subsequent waves of the SARS-CoV-2 epidemic and the limitations from previous studies, we aimed to investigate whether SARS-CoV-2 incidence differed between individuals of South-Asian Surinamese, African Surinamese, Ghanaian, Turkish, Moroccan and Dutch origin living in Amsterdam, specifically during the first and second waves of the Dutch SARS-CoV-2 epidemic. Using longitudinal seroprevalence data nested within the large, population-based cohort study HEalthy Life in an Urban Setting (HELIUS), 13 we compared the SARS-CoV-2 incidence between ethnic groups and identified determinants of incident infection within ethnic groups in Amsterdam, the Netherlands.…”
Section: Introductionmentioning
confidence: 99%